Thoughts on a Changing Landscape for Research Archiving in the Cloud Era: A Critical Perspective from South Africa - (:unkn) unknown (My University, 2023)
This article reflects on humanities research and archival futures in Southern Africa in the Cloud era—those collections that support research on an institutionalised basis, including sound and related collections. Since the 1990s, for comparably smaller, lesser resourced institutions in South Africa, a scramble for digital Africa amid a technological divide piled upon other inequities. This condition has manifested in today’s big technology stacks and stakes. What then, does it mean for archives and their work of helping to produce the conditions for a meaningful engagement with the past and the present, indeed the future? A major challenge for research archives, it seems, may be to do the work of enabling epistemic access, which includes an orientation to ethics from the south, with the new set of vocabularies of digital sovereignty on the other hand. It is also crucial to redefine archival restitution as a social process in which the sovereignty of local communities, digital and otherwise, matters.
Keywords: African Research